Experimental study on detailed emissions speciation of an HCCI engine equipped with a three-way catalytic converter. (15th December 2016) - Hunicz, Jacek; Medina, Alejandro
Abstract: The purpose of the current study is to provide comprehensive quantitative data on hydrocarbon species concentrations in exhaust gases from a homogeneous charge compression ignition (HCCI) engine fuelled with gasoline. Additionally, the obtained results yielded assessment of the efficiency of a standard three-way catalytic converter (TWC) for this kind of engines. Experiments were performed on a single cylinder direct injection engine with ability to be operated in a negative valve overlap mode, to achieve HCCI combustion. The engine was run under variable operating conditions and mixture formation strategies, which provided different compositions of cylinder-out exhaust gases. Fourier transform infrared gas analytical system was used for measurements of exhaust gas compositions. The results showed how different control strategies and injection timings during NVO affect the compositions of unburnt hydrocarbons. To provide a baseline for HCCI results, the research engine was also operated in spark ignition combustion mode. Measurements of exhaust compositions upstream and downstream TWC revealed low conversion efficiency in terms of hydrocarbons oxidation for HCCI combustion. Obtained results indicate that besides reduction of regulated toxic compounds, emissions of specific hydrocarbons could be problematic in the light of future applications of HCCI combustion systems. Highlights: Detailed exhaust speciation from gasoline engine in HCCI and SI modes was provided. Exhaust hydrocarbon structure varied between HCCI and SI combustion. Injection timing during negative valve overlap affected hydrocarbon structure. Catalytic converter exhibited low efficiency for exhaust from HCCI combustion. Conversion of methane was inhibited by acetylene.